2021
DOI: 10.1186/s12886-021-01977-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optical coherence tomography angiography parameters in patients treated with Hydroxychloroquine

Abstract: Background One of the major side effects of Hydroxychloroquine (HCQ) is retinopathy. The aim of this study was to evaluate the Optical coherence tomography angiography (OCTA) parameters in a group of patients who have Hydroxychloroquine-induced retinopathy based on Multifocal electroretinography (mfERG) with a group who do not have retinopathy. Method This is a Cross-Sectional Study. In this study, patients with Rheumatoid arthritis (RA) or Systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…3,4,6,22 The majority of the authors conclude that VD decreased in SCP, DCP and CC in patients taking HCQ for more than 5 years. 1,3,4,6,11,13,18,22,23 In our investigation, we observed that VD in the temporal quadrant of SCP, and total VD and superior VD in MCP were increased in the low-risk group compared to control patients. Moreover, VD in the nasal area of SCP, parafoveal and nasal VD in MCP, and parafoveal and inferior VD of TCP were increased in the highrisk group compared to control group.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…3,4,6,22 The majority of the authors conclude that VD decreased in SCP, DCP and CC in patients taking HCQ for more than 5 years. 1,3,4,6,11,13,18,22,23 In our investigation, we observed that VD in the temporal quadrant of SCP, and total VD and superior VD in MCP were increased in the low-risk group compared to control patients. Moreover, VD in the nasal area of SCP, parafoveal and nasal VD in MCP, and parafoveal and inferior VD of TCP were increased in the highrisk group compared to control group.…”
Section: Discussionmentioning
confidence: 49%
“…These results agree with previous research. 1,3,4,6,11,13,18,22,23 It is known that tall RPE cells with increased melanin contribute to the formation of FAZ. We suggest that the binding of HCQ to melanin of RPE cells may enlarge the FAZ area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, Bulut et al ( 27 ) suggested that OCTA evaluation has the potential to detect hydroxychloroquine-induced retinal toxicity at an early stage. A recent study showed that the mean vascular density in the deep capillary plexus layer decreased in those showing abnormal mfERG recordings, indicating a potential role of OCTA in the early detection of retinopathy ( 28 ). Moreover, another recent report showed a large number of signal void zones in the choriocapillaris of patients with hydroxychloroquine retinopathy, which were more remarkable in those with severe disease ( 15 ).…”
Section: Advanced Optical Coherence Tomography-based Analysismentioning
confidence: 99%